A venda da Vale e a crise de 2008:a cobertura do jornal O Globo em dois momentos do neoliberalismo - Silveira, Matilde Soares da (2011)
This research aims to comparatively analyze the coverage by the newspaper O Globo of two economic events: the sale of Vale do Rio Doce Company on May 6, 1997, and the economic crisis of 2008, triggered from September 15, 2008, when it was requested the bankruptcy of U.S. investment bank Lehman Brothers. The first is a national event that has become the symbol of implementation of neoliberal economic model in Brazil the sale of a company that represented what was then considered excessive state presence in economy. The second refers to the global economic crisis generated from the United States that provoke a desperate demand by some of the large companies, global banking and financial institutions facing bankruptcy for state resources, contradicting the idea that neoliberalism condemns state economic intervention. This research aims to compare, by mapping of the press reports held, the conditions of production, discursive strategies employed and roles played by newspaper and journalist before society in this two occasions.